Empowerment and Assistance for Mosque Management to Create a Regional Technical Implementation Unit (UPTD) for the Ruhama Takengon Grand Mosque - Suwarno, Suwarno; Nur, Ismet; Ali, Ramsah; Sufrizal, Sufrizal (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Mosques are places where Muslims gather. Since the time of Rasulullah saw., mosques have been the basis for the development of Islam. However, currently, most mosques only function as places of worship, because mosque management is less than optimal and lacks innovation. Therefore, as academics with an Islamic education background, we strive to empower and assist mosque management. The location of the dedication is the Great Ruhama Takengon mosque. This service aims to empower and assist mosque management to realize the Great Ruhama Takengon Mosque as a UPTD Mosque. The service method is carried out using Participation Action Research (PAR) and participant observation in the sense that the service member is directly involved in the activity and becomes a resource person in the group discussion forum (FGD), as well as the service member being the perpetrator of the activity. The results of the service show that the mentoring program is very beneficial for the formation of the UPTD of the Ruhama Takengon Grand Mosque and needs to continue and even be improved until the issuance of the UPTD Decree from the Regent of Central Aceh